Surface treatments of titanium and zirconia implants: Literature review (Research, Society and Development, 2021)
The different surface treatments on dental implants have the premise of improving the contact interface between bone and implant, accelerating the osseointegration process. The purpose of this literature review was to verify the different types of surface treatments for titanium and zirconia dental implants, their characteristics and actions on osseointegration. For this, researches were carried out in the national and international databases: PUBMED, SciELO and Google Scholar. The data found demonstrate that in both titanium and zirconia implants, the surfaces can be modified, with the aim of improving biological performance by accelerating the initial healing process, in order to promote an initial stability superior to untreated implants. In addition, changes that promote greater surface energy, increasing wettability and hydrophilicity present greater adhesion and proliferation of osteoblasts and, consequently, a more accelerated bone neoformation, which contribute to this initial process of healing and osseointegration. Despite the variability in the types of treatment, some of which are in common with titanium and zirconia, the changes have proven to be effective, allowing loading in less time. The choice of surface treatment can be determined by bone quality, systemic conditions of the patient and the type of pre-planned loading. Regarding zirconia implants, the studies are promising, but long-term studies are necessary, as there is not yet enough data to clearly and safely indicate the use of these implants, except in cases of proven allergenicity to titanium.